Qualidade na prestação de serviço: avaliação por meio da ferramenta Servqual em uma padaria - Dias, Maria Tereza Morais Medeiros (Universidade Federal Rural do Semi-Árido, 2019)
Identify organizational failures, know the expectations and perceptions of customers through the services provided by a company, puts into question the quality offered by the organization and its effectiveness. Thus, the present study has as objective to analyze the perception and expectation of the clients in relation to the services provided within the framework of the Servqual scale at São Pedro’s Bakery, located in the city of Assú, Rio Grande do Norte. As far as the methodology was concerned, it was based on a quantitative research, of an exploratory and descriptive nature, of the case study type. A questionnaire was adopted as a research instrument, in which the Servqual scale was adequate to execution. 84 clients of the Bakery were interviewed, in such a way that they expressed their wishes and perceptions regarding the services provided. The results showed that, in general, the company showed an unsatisfactory level of quality to the customers, so there are Gaps (failures) that need to be corrected, especially in terms of tangibility and safety. The implementation of an action plan of type 5W1H was carried out to measure the problems identified. Therefore, it is concluded that São Pedro’s Bakery needs to review its weaknesses and correct the gaps through the dimensions, so that its performance can be in accordance with what the consumers expect.
Artigo
Keywords: Servqual; Serviço; Dimensão; Qualidade; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA